A novel locus for exertional dyspnoea in childhood asthma. Issue 2 (4th February 2021) - Lee, Sanghun; Lasky-Su, Jessica Ann; Lange, Christoph; Kim, Wonji; Kumar, Preeti Lakshman; McDonald, Merry-Lynn N.; Vaz Fragoso, Carlos A.; Laurie, Cecelia; Raby, Benjamin A.; Celedón, Juan C.; Cho, Michael H.; Won, Sungho; et al.
Most children diagnosed with asthma have respiratory symptoms such as cough, dyspnoea and wheezing, which are also important markers of overall respiratory function. A decade of genome-wide association studies (GWAS) have investigated genetic susceptibility to asthma itself, but few have focused on important respiratory symptoms that characterise childhood asthma. Using whole-genome sequencing (WGS) data for 894 asthmatic trios from a Costa Rican cohort, we performed family-based association tests (FBATs) to assess the association between genetic variants and multiple asthma-relevant respiratory phenotypes: cough, phlegm, wheezing, exertional dyspnoea and exertional chest tightness. We tested whether genome-wide significant associations were replicated in two additional studies: 1) 286 asthmatic trios from the Childhood Asthma Management Program (CAMP), and 2) 2691 African American current or former smokers from the COPDGene study. In the 894 Costa Rican trios, we identified a genome-wide significant association (p=2.16×10 −9 ) between exertional dyspnoea and the single nucleotide polymorphism (SNP) rs10165869, located on chromosome 2q37.3, that was replicated in the CAMP cohort (p=0.023) with the same direction of association (combined p=3.28×10 −10 ). This association was not found in the African American participants from COPDGene. We also found suggestive evidence for an association between SNP rs10165869 and the atypical chemokine receptor 3 ( ACKR3 ). Our finding encourages the secondary association analysis of a wider range of phenotypes that characterise respiratory symptoms in other airway diseases/studies. WGS data from a family-based association study suggest that the replicated SNP variant rs10165869 is associated with exertional dyspnoea, likely through the expression of ACKR3 https://bit.ly/3a5ddBd